The effect of value-added human capital, structural capital value-added, value-added capital employed, and profitability on firm value with firm size as a moderating variable (Study of manufacturing companies in the sub-sector pharmaceuticals listed on th - Putri, Ashiilah Atika (International Journal of Economic, Business & Applications, 2024)
This study, which focuses on pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2021, aims to determine the effect of value-added human capital, structural capital value-added, value-added capital employed, and profitability on firm value, moderated by firm size. The sample selection in this study used the purposive sampling method, resulting in eight companies based on predetermined criteria. The data analysis method used is moderation regression analysis. The results showed that value-added human capital significantly positively affects firm value, while structural capital value added has a significant negative effect on firm value. Value-added capital employed has a significant positive effect on firm value, and profitability has an insignificant positive effect on firm value. Firm size weakens the effect of value-added human capital on firm value, strengthens the effect of structural capital value added on firm value, weakens the effect of value-added capital employed on firm value, and does not moderate the effect of profitability on firm value.